Analysis Of Raw Material Inventory Control Of Polyester Yarn Using The Economic Order Quantity (Eoq) Method At Cv Intan Ciwangi, Bandung Regency - Rinita Pujiawati; Leo Simanulang (Jurnal Ilmu Ekonomi, Pendidikan dan Teknik, 2026)
Inventory control of raw materials is a crucial factor in maintaining operational efficiency in manufacturing companies. CV Intan Ciwangi, located in Bandung Regency, still applies conventional methods in managing polyester yarn raw material inventory, resulting in inefficient inventory costs. This study aims to analyze inventory control using the Economic Order Quantity (EOQ) method. The research method used is qualitative with a case study approach. Data collection techniques include observation, interviews, and documentation. The results show that the optimal order quantity based on EOQ is 3,659 kg with an ordering frequency of 4 times per period and total inventory costs of Rp896,460. The implementation of EOQ has proven to improve efficiency and reduce inventory costs compared to the company’s current method.